2018
DOI: 10.1016/j.jtho.2018.08.1579
|View full text |Cite
|
Sign up to set email alerts
|

P3.01-19 Sequencing of Ramucirumab+Docetaxel Post-Immune Checkpoint Inhibitors in Advanced Non-Small Cell Lung Cancer Patients

Abstract: Background: The anti-programmed cell death 1 (PD-1) immune checkpoint inhibitors, nivolumab and pembrolizumab, are currently approved for the treatment of patients with NSCLC. The PD-L1 expression represents the most validated predictive marker of response to PD-1 inhibitors. However, there are several different immunohistochemical assays to assess the PD-L1 expression using different antibodies, platforms, and cutoff values. We compared the PD-L1 expression evaluated by IHC 22C3 PharmDx with that observed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, based on what is known regarding mechanism of action, the efficacy and safety profile for ramucirumab plus docetaxel following both immunotherapy and chemotherapy in the first line is expected to be consistent with what was observed in REVEL. There are ongoing efforts to use real-world evidence to evaluate outcomes for ramucirumab plus docetaxel in the postimmunotherapy setting,32 33 and additional studies are needed to specifically evaluate outcomes for ramucirumab plus docetaxel following immuno-oncology and chemotherapy combinations in the first line.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on what is known regarding mechanism of action, the efficacy and safety profile for ramucirumab plus docetaxel following both immunotherapy and chemotherapy in the first line is expected to be consistent with what was observed in REVEL. There are ongoing efforts to use real-world evidence to evaluate outcomes for ramucirumab plus docetaxel in the postimmunotherapy setting,32 33 and additional studies are needed to specifically evaluate outcomes for ramucirumab plus docetaxel following immuno-oncology and chemotherapy combinations in the first line.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a statistically significant improvement in real-world DCR was observed when compared to ramucirumab plus docetaxel given after other non–ICIs (80.7% vs 54.4%; P <0.01) ( 45 ). Furthermore, in a cohort of patients treated with third-line ramucirumab plus docetaxel after ICI treatment, median real-world PFS (measured from the start of third-line ramucirumab plus docetaxel) was 3.6 months (range: 3.0-4.6 months) while median real-world OS (measured from the start of first-line therapy) was 19 months (range: 15.7-23.7 months) ( 47 ). The TREAT-LUNG study, a large retrospective observational study that collected data from 3 electronic health record-derived databases, investigated efficacy outcomes of second- or third-line therapy with ramucirumab plus docetaxel administered after prior chemotherapy plus ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 11 studies were excluded from the efficacy analysis because they did not meet the inclusion criteria. However, results from these excluded studies also indicated that ramucirumab plus docetaxel was a safe and efficacious treatment after prior treatment with ICIs (35,37,42,(45)(46)(47)(67)(68)(69)(70). Five of these were real-world studies that used electronic health record-derived databases were not included in the efficacy analysis because they did not meet the SLR inclusion criteria (45)(46)(47)71) or they had a high percentage of missing data (e.g., tumor response assessment) and therefore had a high potential for misclassification and residual confounding bias (72).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations